EFFECT OF TRANSPLANTING METHODS, NP- FERTILIZER RATES ON CANOPY WIDTH OF FEMALE DATE PALM (PHOENIX DACTYLIFERA L.) OFFSHOOT (FUDMA JOURNAL OF SCIENCES, 2020)
Studies on the effect of transplanting methods and NP â€“ fertilizer rates on canopy width of a female date palm offshoot have been conducted over a period of 25 months (September, 2017 â€“ September 2019). The trial was sited at the Date Palm Research Sub â€“ station/ Federal University Dutse (11o50â€™N, 09o25â€™E) in the Sudan Savanna ecological zone of Nigeria. The treatments consisted of two transplanting methods (Direct: detachment of offshoot from the parent palm and directly transplanting into the field, and Indirect: detachment of offshoot from the parent palm and keeping in the nursery for 3 months before transplanting into the field) and five NP fertilizer rates Control (0g N + 0g P), 80g N + 40g P, 160g N + 80g P, 240g N +120g P and 320g N + 160g P) arranged in a randomized complete block design with three replications. Canopy width was measured and recorded at three monthsâ€™ interval starting from September, 2017 to September 2019. Indirect transplanting of date palm through nursery proved more effective than direct transplanting as it produces statistically wider canopies in all the sampled periods. Rate 320g N +160g P statistically outperformed other rates in promoting wider canopies throughout the sampling periods. A combination of indirect transplanting method with rate 320g N +160g P that produced wider canopies is recommended for adoption  in the Sudan Savannah ecological zone of Nigeria.
Keywords: Date palm offshoot, direct transplanting method, indirect transplanting method NP- fertilizer and canopy width.